2022
DOI: 10.1155/2022/1585840
|View full text |Cite
|
Sign up to set email alerts
|

Neural Peptide α-CGRP Coregulated Angiogenesis and Osteogenesis via Promoting the Cross-Talk between Mesenchymal Stem Cells and Endothelial Cells

Abstract: Background. The coupled vascularization and bone remodeling are key steps during bone healing, during which the cross-talk between mesenchymal stem cells (MSCs) and endothelial cells plays vital roles. Evidence indicates the well-characterized neuropeptide Calcitonin Gene-Related Peptide-α (CGRP) is proven to play an important role during bone regeneration. However, the regulatory effects of αCGRP on angiogenesis and osteogenesis, as well as underlying cellular and molecular mechanisms, remain unclear. Aim. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…It is noteworthy that in this study dentine injury evoked an intense in‐growth of newly formed CGRP‐labelled nerve fibres at an early stage, and blocking CGRP signalling led to a reduction in CD31 + vessels and type H vessels, followed by impaired reparative dentine formation. An ex vivo study confirmed that CGRP treatment increases nitric oxide synthase expression, nitric oxide release, and the migratory ability of endothelial cells (Shi et al., 2022). This effect on migration and tube formation of endothelial cells is comparable to that of the known angiogenesis regulator vascular endothelial growth factor (VEGF) (Tuo et al., 2013).…”
Section: Discussionmentioning
confidence: 82%
“…It is noteworthy that in this study dentine injury evoked an intense in‐growth of newly formed CGRP‐labelled nerve fibres at an early stage, and blocking CGRP signalling led to a reduction in CD31 + vessels and type H vessels, followed by impaired reparative dentine formation. An ex vivo study confirmed that CGRP treatment increases nitric oxide synthase expression, nitric oxide release, and the migratory ability of endothelial cells (Shi et al., 2022). This effect on migration and tube formation of endothelial cells is comparable to that of the known angiogenesis regulator vascular endothelial growth factor (VEGF) (Tuo et al., 2013).…”
Section: Discussionmentioning
confidence: 82%
“…CGRP and SP have already been confirmed as the supportive factors of angiogenesis process 135 . CGRP coupled angiogenesis and osteogenesis by promoting the crosstalk between MSCs and ECs via initiating the cAMP‐signaling pathway 20 . CGRP induces a higher expression level of angiogenic factors, including fibroblast growth factor (FGF) and VEGF.…”
Section: Sensory Nerves and Skeletonmentioning
confidence: 99%
“…16,17 In addition, neural pathways have been found to regulate matrix deposition during skeletal development, which is activated in response to paracrine/autocrine processes. [18][19][20][21][22][23] In turn, bone tissue provides accommodation for peripheral nerves, acts as a scaffold, and actively participates in neuroregulation. Thus, the bone and nerve indeed support each other, implying a neuro-osteogenic network.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CGRP is also a factor that promotes angiogenesis and lymph angiogenesis. Lin et al encapsulated CGRP in poly­(lactic- co -glycolic acid) (LGA) nanoparticles and found that the release of CGRP could restore the levels of CGRP and vascular inflammatory factors in rats. Gong et al studied the regulatory mechanism of CGRP on angiogenesis and osteogenesis. The results showed that CGRP could significantly increase the level of cyclic adenosine monophosphate (cAMP) in MSCs by regulating the cAMP/PKA signaling pathway and promoting the osteogenic ability of MSCs.…”
Section: Introductionmentioning
confidence: 99%